Steeper spatial scaling patterns of subsoil microbiota are shaped by deterministic assembly process. Issue 4 (26th December 2020) - Du, Xiongfeng; Deng, Ye; Li, Shuzhen; Escalas, Arthur; Feng, Kai; He, Qing; Wang, Zhujun; Wu, Yueni; Wang, Danrui; Peng, Xi; Wang, Shang
Abstract: Although many studies have investigated the spatial scaling of microbial communities living in surface soils, very little is known about the patterns within deeper strata, nor is the mechanism behind them. Here, we systematically assessed spatial scaling of prokaryotic biodiversity within three different strata (Upper: 0–20 cm, Middle: 20–40 cm, and Substratum: 40–100 cm) in a typical grassland by examining both distance–decay (DDRs) and species–area relationships (SARs), taxonomically and phylogenetically, as well as community assembly processes. Each layer exhibited significant biogeographic patterns in both DDR and SAR ( p  < .05), with taxonomic turnover rates higher than phylogenetic ones. Specifically, the spatial turnover rates, β and z values, respectively, ranged from 0.016 ± 0.005 to 0.023 ± 0.005 and 0.065 ± 0.002 to 0.077 ± 0.004 across soil strata, and both increased with depth. Moreover, the prokaryotic community in grassland soils assembled mainly according to deterministic rather than stochastic mechanisms. By using normalized stochasticity ratio (NST) based on null model, the relative importance of deterministic ratios increased from 48.0 to 63.3% from Upper to Substratum, meanwhile a phylogenetic based method revealed average βNTI also increased with depth, from −5.29 to 19.5. Using variation partitioning and distance approaches, both geographic distance and soil properties were found to strongly affect biodiversity structure, the proportions increasing with depth, but spatial distance was always the main underlying factor. These indicated increasingly deterministic proportions in accelerating turnover rates for spatial assembly of prokaryotic biodiversity. Our study provided new insights on biogeography in different strata, revealing importance of assembly patterns and mechanisms of prokaryote communities in below‐surface soils.